Factors Influencing Selection of Oral Hygiene Aids Among an Urban Population of Kathmandu District - Khanal, Sunita; Bhattarai, Rosina; Shrestha, Sujita; Rao, G. Nagaraja (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Introduction: The exact origin of mechanical device for cleaning teeth is not known. In past, plants with high aromatic properties were chewed by people in twigs form. These twigs freshened breath and spread out fibres at their tips as they were used for cleaning teeth and gum surfaces. China was the first country to invent toothbrush. Widely used oral hygiene aids are toothbrush and toothpaste. Objective: To assess the factors influencing selection of oral hygiene aids among an urban population of Kathmandu district. Methods: A cross-sectional analytical study was conducted during July-October 2019 among the adult population from outreach programs and outpatient department of Kantipur Dental College Teaching Hospital after receiving ethical approval from Institutional Review Committee. Convenience sampling was done. A predesigned questionnaire was used for data collection purpose. Data was entered in Microsoft Excel and analysed using SPSS v.20 software. Chi-square test was done at ≤ 0.05 level of significance. Results: Among 301 participants, 133 (44.2%) were male and 168 (55.8%) were female. The factors that influenced selection of toothpaste were: taste 169 (56.1%), fluoride content 160 (53.2%), previous experience 209 (69.4%), dentist’s advice 180 (59.8%). Factors that influenced selection of toothbrush were: texture of bristle 274 (91%), cost of toothbrush 169 (56%), brand 211 (70%), previous experience, 200 (66.4%), 184 (61%) by size of head of toothbrush, and 184 (61.1%) by dentist’s advice. Conclusion: Previous experience, cost, and dentist’s advice seemed influential factors in the choice of oral hygiene aids among the urban population of Kathmandu district.